2021
DOI: 10.1007/s40430-021-03039-9
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of thrust plate tilt on performance of distributed hybrid thrust bearing with tilting pad

Abstract: A kind of distributed hybrid thrust bearing with tilting pad is proposed in this paper, and the influence of thrust plate tilt on bearing performance is analyzed. The film thickness equation is constructed, considering the machining error and installation error synthetically which are the main causes of thrust plate tilt. Substituting the film thickness equation to the classical calculation equation of thrust bearing, the time-varying stiffness of the bearing is obtained. The influence of tilt angle of thrust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…7 As the misalignment angle increased, the thrust plate tilt caused a fluctuation of the bearing stiffness during the rotation period, which was exacerbated by an increase in the tilt angle. 8 For self-equalizing TPTBs, Gokaltun and DeCamillo 9 developed a finite element analysis (FEA) model to represent the interaction between the thrust bearing components under the influence of a misaligned rotor and suggested that the leveling mechanism worked more effectively at higher loads; Koosha and San Andrés 10 performed a comprehensive multiple-pad analysis to evaluate the performance of self-equalizing TPTBs accurately, and found that an ideal self-equalizing TPTB (without friction at the contacts) operated with larger minimum fluid film thickness and lower peak film pressure compared to those obtained in a non-equalizing bearing.…”
Section: Introductionmentioning
confidence: 99%
“…7 As the misalignment angle increased, the thrust plate tilt caused a fluctuation of the bearing stiffness during the rotation period, which was exacerbated by an increase in the tilt angle. 8 For self-equalizing TPTBs, Gokaltun and DeCamillo 9 developed a finite element analysis (FEA) model to represent the interaction between the thrust bearing components under the influence of a misaligned rotor and suggested that the leveling mechanism worked more effectively at higher loads; Koosha and San Andrés 10 performed a comprehensive multiple-pad analysis to evaluate the performance of self-equalizing TPTBs accurately, and found that an ideal self-equalizing TPTB (without friction at the contacts) operated with larger minimum fluid film thickness and lower peak film pressure compared to those obtained in a non-equalizing bearing.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic characteristics of the bearing have a great influence on the dynamic behavior of the rotor system. The dynamic characteristics coefficients can be obtained by theoretical calculation [3]. However, the theoretical calculation formula of the dynamic characteristics coefficients of hydrostatic bearing stiffness is the approximate formula [4], which deviates the actual operating state.…”
Section: Introductionmentioning
confidence: 99%
“…Badawi et al 6 studied the influence of the tilting pads number and the pads gap on the performance of tilting pad journal bearings, the results show that with the decrease of the pad gap, the bearing capacity increase. Chen et al 7 proposed a tilting pad distributed hybrid thrust bearing, and showed that with the increase of the preload coefficient of the tilting pad, the stiffness of the thrust bearing gradually increased, when the preload coefficient reached a certain value, the performance of the thrust bearing will decrease.…”
Section: Introductionmentioning
confidence: 99%